Assessing the Severity of Illness in Patients With Coronavirus Disease in Saudi Arabia: A Retrospective Descriptive Cross-Sectional Study - Alqahtani, Abdulhadi M.; AlMalki, Ziyad S.; Alalweet, Randah M.; Almazrou, Saja H.; Alanazi, Abdullah Salah; Alanazi, Mona A.; AlShehri, Abdussalam A.; AlGhamdi, Saleh (Frontiers in Public Health, 2020)
Objectives: We aimed to describe the epidemiological and clinical characteristics of patients with COVID-19 in Saudi Arabia in various severity groups.Methods: Data for 485 patients were extracted from the medical records from the infectious disease center of Prince Mohammed bin Abdul Aziz Hospital in Riyadh. Patients’ basic information, laboratory test results, signs and symptoms, medication prescribed, other comorbidities, and outcome data were collected and analyzed. Descriptive data were reported to examine the distribution of study variables between the severe and not severe groups. Results: Of 458 included patients, 411 (89.7%) were classified as not severe, 47 (10.2%) as severe. Most (59.1%) patients were aged between 20 and 39 years. Patients with severe conditions were non-Saudi, with a chronic condition history, and tended to have more chronic conditions compared with those without the severe disease. Diabetes, hypertension, and thyroid disease were significantly higher in patients with severe disease. Death was reported in only 4.26% of severe patients. Only 16 (34.04%) patients remained in the hospital in the severe group. Conclusions: Severe cases were more likely to have more comorbidities, diabetes, hypertension, and thyroid disorders were most common compared with non-severe cases.